2018
DOI: 10.1007/s00772-018-0465-x
|View full text |Cite
|
Sign up to set email alerts
|

Short version of the S3 guideline on screening, diagnosis, therapy and follow-up of abdominal aortic aneurysms

Abstract: Short version of the S3 guideline on screening, diagnosis, therapy and follow-up of abdominal aortic aneurysms On 3 July 2018, under the leadership of the German Society for Vascular Surgery and Vascular Medicine (DGG), the new S3 guidelines for screening, diagnosis, treatment, and follow-up for abdominal aortic aneurysms (AAA) were adopted by the DGG Executive Board, after unanimous approval by all participating profes

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 117 publications
0
10
0
1
Order By: Relevance
“…These findings indicate that in the absence of a valid German S3 guideline for treatment of AAA, clinical practice varied greatly in Germany during the observation period, despite the valid European Guideline [24]. It will be interesting to see whether treatment methods are harmonizing since publication of the German guideline in 2018 [2]. However, due to the administrative character of the dataset, the underlying indications for EVAR or OAR cannot be fully identified and comprehended in the light of applicable guidelines and practices.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings indicate that in the absence of a valid German S3 guideline for treatment of AAA, clinical practice varied greatly in Germany during the observation period, despite the valid European Guideline [24]. It will be interesting to see whether treatment methods are harmonizing since publication of the German guideline in 2018 [2]. However, due to the administrative character of the dataset, the underlying indications for EVAR or OAR cannot be fully identified and comprehended in the light of applicable guidelines and practices.…”
Section: Discussionmentioning
confidence: 99%
“…To prevent rupture, either the affected vessel segment can be replaced with a prosthesis in an open approach (open aortic repair, OAR) or treatment may be endovascular, by implanting a stent graft (endovascular aortic repair, EVAR). According to current guidelines, treatment is indicated when an AAA exceeds 55 mm in diameter, but might be performed earlier in some cases [2,3]. In Germany, however, many cases are treated below this threshold [4].…”
Section: Introductionmentioning
confidence: 99%
“…However, precise rupture prediction for the individual AAA remains a challenge, and is currently based on epidemiological and morphological data. 11,13 In previous studies, WMIs, obtained by mechanical modelling and statistical analysis based on 4D ultrasound measurements, have been proposed as mechanical biomarkers for the pathophysiological state of the individual AAA wall. In the current study, WMIs are shown to be capable of characterising the kinematic differences between AAA sac and neck non-invasively in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Although open surgical repair is supported as the gold standard for mycotic aortic aneurysms in current aortic aneurysm guidelines, endovascular repair is recommended as an alternative 23 , 24 owing to early survival benefit up to 4 years postoperatively. 25 We consider EG impregnation with RIF in such cases as legitimate in addition to systemic antibiotic therapy.…”
Section: Discussionmentioning
confidence: 99%